Disruption of the circadian period of body temperature by the anesthetic propofol. (20th October 2016) - Touitou, Yvan; Mauvieux, Benoit; Reinberg, Alain; Dispersyn, Garance
ABSTRACT: The circadian time structure of an organism can be desynchronized in a large number of instances, including the intake of specific drugs. We have previously found that propofol, which is a general anesthetic, induces a desynchronization of the circadian time structure in rats, with a 60–80 min significant phase advance of body temperature circadian rhythm. We thus deemed it worthwhile to examine whether this phase shift of body temperature was related to a modification of the circadian period Tau. Propofol was administered at three different Zeitgeber Times (ZTs): ZT6 (middle of the rest period), ZT10 (2 h prior to the beginning of activity period), ZT16 (4 h after the beginning of the activity period), with ZT0 being the beginning of the rest period (light onset) and ZT12 being the beginning of the activity period (light offset). Control rats ( n = 20) were injected at the same ZTs with 10% intralipid, which is a control lipidic solution. Whereas no modification of the circadian period of body temperature was observed in the control rats, propofol administration resulted in a significant shortening of the period by 96 and 180 min at ZT6 and ZT10, respectively. By contrast, the period was significantly lengthened by 90 min at ZT16. We also found differences in the time it took for the rats to readjust their body temperature to the original 24-h rhythm. At ZT16, the speed of readjustment was more rapid than at the two other ZTs that we investigated. This study hence shows (i) the disruptive effects of the anesthetic propofol on the body temperature circadian rhythm, and it points out that (ii) the period Tau for body temperature responds to this anesthetic drug according to a Tau-response curve. By sustaining postoperative sleep–wake disorders, the disruptive effects of propofol on circadian time structure might have important implications for the use of this drug in humans.